An Anticipative Control Approach and Interactive GUI to Enhance the Rendering of the Distal Robot Interaction with its Environment during Robotized Tele-Echography: Interactive Platform for Robotized Tele-Echography - Vieyres, Pierre; Sandoval, Juan; Josserand, Laurence; Novales, Cyril; Chiccoli, Marco; Morette, Nicolas; Fonte, Aicha; Avgousti, Sotiris; Voskarides, Sotos; Kasparis, Takis (My University, 2013)
Performing a robotized telemedicine act via specific networks brings forth the issue of transparency in order to enable the operator, e.g. the medical ultrasound specialist, to safely and accurately perform bilateral tele-operation tasks despite the long time delays inherent to the communication link. To counter these effects, two strategies are combined to improve, at the operator site, the rendering of the interactions between the remote robotic systems with its environment (i.e. the patient), and the control of the robot’s orientation at the operator site. The first approach is the development of a new control architecture based on an internal model providing an anticipated value of the distant environment stiffness; it is complemented with a graphic user interface (GUI) which provides the expert with the real-time relative position of the haptic probe with the robot’s end effector for better tele-operated control. These combined strategies provide the expert with an improved interactive tool for tele-diagnosis.
Keywords: Robotized telemedicine; Telemedicine